Epidemiological study of cervical cord compression and its clinical symptoms in community-dwelling residents - Hirai, Toru; Otani, Koji; Sekiguchi, Miho; Kikuchi, Shin-ichi; Konno, Shin-ichi (PloS one, 2021)
Degenerative compressive myelopathy (DCM) is caused by cervical cord compression. The relationship between the magnitude and clinical findings of cervical cord compression has been described in the literature, but the details remain unclear. This study aimed to clarify the relationship between the magnitude and clinical symptoms of cervical cord compression in community-dwelling residents. The present study included 532 subjects. The subjective symptoms and the objective findings of one board-certified spine surgeon were assessed. The subjective symptoms were upper extremity pain and numbness, clumsy hand, fall in the past 1 year, and subjective gait disturbance. The objective findings were: Hoffmann, Trömner, and Wartenberg signs; Babinski's and Chaddock's signs; hyperreflexia of the patellar tendon and Achilles tendon reflexes; ankle clonus; Romberg and modified Romberg tests; grip and release test; finger escape sign; and grip strength. Using midsagittal T2-weighted magnetic resonance imaging, the anterior-posterior (AP) diameters (mm) of the spinal cord at the C2 midvertebral body level (DC2) and at each intervertebral disc level from C2/3 to C7/T1 (DC2/3-C7/T1) were measured. The spinal cord compression ratio (R) for each intervertebral disc level was defined and calculated as DC2/3-C7/T1 divided by DC2. The lowest R (LR) along C2/3 to C7/T1 of each individual was divided into 3 grades by the tertile method. The relationship between LR and clinical symptoms was investigated by trend analysis. The prevalence of subjective gait disturbance increased significantly with the severity of spinal cord compression (p = 0.002812), whereas the other clinical symptoms were not significantly related with the severity of spinal cord compression. The magnitude of cervical cord compression had no relationship with any of the neurologic findings. However, subjective gait disturbance might be a better indicator of the possibility of early stage cervical cord compression.